Money as a Medium of Exchange: Then and Now: Can Technology Be A Facilitator of Exchange? (Global Journal of Management and Business Research, 2016)
This paper deals with the origin of money through its function as a medium of exchange. Barter can give rise to money through necessitating the use of a standard of value even before calling for the use of a medium of exchange. In a given society at any point in time money is defined in principle simply as the subset of total financial assets and commodities which are actually performing monetary functions. Three main functions are usually suggested. Money is thought to be that which serves as a medium of exchange, standard of value and store of value. Defining money in a particular context would simply involve a judgment as to which items currently possess these properties to a greater or lesser extent. The paper also ascertains whether money originated through its function as a medium of exchange, can explain the dynamics of monetary exchange of most recent days. The paper also ascertains if technological changes can improve the efficiency of the trading process.
Keywords: medium of exchange; standard of value; store of value gresham’s law.